(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Mahasweta Devi’s works discussed below clearly reflect the author’s concern for the underprivileged who are deprived of their basic rights by the dominant upper classes. Devi ’s works do not present a glorified image of the own-trodden, but they certainly present their lives in the midst of adversity and show their spirit and strength to resist any form of social oppression. In order to understand Mahasweta Devi ’s discourse on class , caste and gender oppression and her portrayal of the spirit of the oppressed, the researcher quotes from Gail Omvedt, Dalits, and the Democratic Revolution, where the spirit of the oppressed is effectively portrayed Things began to change when someone brought him news of Naxalbari and aroused a spirit of rebellion that created a powe. Such a change indicated above can also be seen in the writings of Mahasweta Devi. Thus, the author’s discourse of class , caste, and gender oppression reveals a unique narrative of the downtrodden, his her oppression, and finally his her resistance to oppression. Such a discourse on class , caste and gender oppression in Mahasweta Devi ’s work is the basic argument of the thesis. In Omvedt ’s book, the awareness of the oppressed in his distress is likened to the situation of a dead man’s resurrection and to his act of cutting off the branches of feudalism. The oppressed are humiliated, whipped, killed and denied the status of a human being. And his wife is being treated like a prostitute.